2022
DOI: 10.1371/journal.pbio.3001668
|View full text |Cite|
|
Sign up to set email alerts
|

The Aedes aegypti siRNA pathway mediates broad-spectrum defense against human pathogenic viruses and modulates antibacterial and antifungal defenses

Abstract: The mosquito’s innate immune system defends against a variety of pathogens, and the conserved siRNA pathway plays a central role in the control of viral infections. Here, we show that transgenic overexpression of Dicer2 (Dcr2) or R2d2 resulted in an accumulation of 21-nucleotide viral sequences that was accompanied by a significant suppression of dengue virus (DENV), Zika virus (ZIKV), and chikungunya virus (CHIKV) replication, thus indicating the broad-spectrum antiviral response mediated by the siRNA pathway… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 91 publications
0
24
0
Order By: Relevance
“…Initially, it was reported that the Toll signalling pathway responded to Gr+ bacteria and fungi, the immune deficiency (IMD) pathway to Gr– bacteria, and the JAK-STAT and RNAi pathways to viruses [ 17 , 18 , 19 , 20 ]. More recent studies have demonstrated that there is plasticity and cross-talk among and between immune pathways that allow strong multifaceted responses to pathogens and parasites [ 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Initially, it was reported that the Toll signalling pathway responded to Gr+ bacteria and fungi, the immune deficiency (IMD) pathway to Gr– bacteria, and the JAK-STAT and RNAi pathways to viruses [ 17 , 18 , 19 , 20 ]. More recent studies have demonstrated that there is plasticity and cross-talk among and between immune pathways that allow strong multifaceted responses to pathogens and parasites [ 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…The mosquitoToll and JAK-STAT immune signaling pathways and the siRNA immune pathway, play important roles in defending against arboviral infections [56,66,67] (reviewed in [68]). Here as proof of principle, we used CRISPRa to transactivate AaRel1, an NF-κB Relish-like transcription factor that mediates the Toll immune pathway's antipathogenic action including the suppression of Dengue and Zika viruses [54][55][56][57].…”
Section: Overexpression Of Aarel1 Results In Virus Suppressionmentioning
confidence: 99%
“…With the rapid development of the tissue-specific dCas9-VPR lines in combinations with targets-specific sgRNA lines in the future, these key immune factors can be studied specifically in a spatio-temporal manner. This tool can be used to boost mosquitoes’ immunity against viral infections by transactivating genes involved in various immune pathways, such as Relish-like transcription factors Rel1 and Rel2, the two key downstream regulators of the Toll and IMD immune pathways [54,72,73], or the insect cytokine-like factor Vago [74,75], or DOME and HOP in the JAK-STAT pathway [67], or Dicer2 and R2d2 in the siRNA immune pathway [66]. The knowledge gained from these basic studies will further strengthen the development of vector control strategies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations